A case report reappraising the usefulness of Valsalva manoeuvre in drug-refractory ventricular tachycardia. Issue 5 (5th May 2021) - Lwin, Tin Sanda; Mitrakrishnan, Rayno Navinan; Alama, Mohamed; Chin, Shui Hao
Abstract: Background: Ventricular tachycardia (VT) is often misdiagnosed as supraventricular tachycardia with aberrancy. Twelve-lead electrocardiogram remains a key diagnostic tool to differentiate them while providing insights to aid localization of VT. The use of Valsalva manoeuvre (VM) in terminating VT is not conventionally recommended due to lack of robust evidence of its effectiveness and poor understanding of its mechanism in terminating VT. Case summary: A 74-year-old man with history of ischaemic heart disease was admitted with broad complex tachycardia. VT-1 was diagnosed following failed tachycardia termination by adenosine. Haemodynamic compromise necessitated synchronized cardioversion with successful reversion. However, a different VT-2 occurred after cardioversion. VM led to successful termination of VT-2. Subsequently, recurrent episodes of VT-2 occurred with consistent termination by VM. Transthoracic echocardiogram, cardiac magnetic resonance imaging, and a coronary angiogram were performed. Findings suggested that these are likely scar-related VT. VT-1 originated from an anteroseptal scar, whilst VT-2, responsive to VM, likely originated from the Purkinje fibres. Patient remained eurhythmic after Day 1 following amiodarone and beta-blocker initiation. An implantable cardioverter-defibrillator was implanted prior to discharge. Discussion: VM is one of the vagal manoeuvres which are commonly used as initial management of supraventricular tachycardia. Its role in management of VT is obscure. Anecdotal case series recorded its successful use for managing particular VT. Exact mechanism remains elusive although postulated to involve change in cardiac size during strain and release of acetylcholine.